The Impact of Electronic Books on Learning English Language in the Digital Era: An Overview - Ghafar, Zanyar (RADINKA JAYA UTAMA PUBLISHER, 2024)
English is an essential skill that must be acquired. It is a globally understood language that facilitates communication between individuals from different countries. There are several methods to achieve proficiency in English; one of them is via reading literature. A textbook serves as both a tool and a means of acquiring knowledge. Reading is a fundamental ability. Interpretation is the cognitive ability or process of extracting meaning or understanding from written or spoken communication. Today, technology is advancing swiftly, making tasks more convenient than ever before. Individuals are no longer need to actively pursue knowledge or be concerned about being in a secluded location devoid of libraries and bookshops. The data was readily accessible on our display, often at no expense, presented in a numerical format. E-books, internationally recognized as digital publications, are texts presented in a digital format. Although they may include graphics and graphs to some extent, their forms mostly make them text-oriented. The findings of the study shows that several benefits to using electronic books, but there are also drawbacks associated with them. However, the process of learning involves acquiring knowledge and effectively using it. The origin of knowledge is boundless; it may arise from any source, at any moment, and include any subject matter.